“Radical”: Marianne Moore and the Revision of Modernism - Aurore Clavier (Transatlantica)
From the editorial birth of Imagism to the preliminary pruning of The Waste Land, the dominant narratives of Modernism have often been built on foundational acts of crossing out, whether self-imposed, collective or allographic. Since they combine the erasure of past verbal excesses and the endeavor of compression on the page, such slashes of the “creative pencil” (H.D.), aptly seem to enact and materialize the revolutionary dynamics of rejection and renewal that most writers and critics have chosen to foreground over alternative paradigms of change. Leading us from the working manuscript to the little magazine, from the individual collection to the endlessly emended magnum opus, from the anthology to the text-book, the practice of revision, then, retraces the historical construction of literary revolution(s), highlighting lines of rupture and continuity as certain names are marginalized or simply deleted.Because, among them, Marianne Moore was herself a relentless editor of her own or others’ words, yet has remained a shifting figure in the “great narrative” of Modernism, her work allows us to re-examine the claims of artistic radicalism, in the light of more complex modes of revision. Although she may indeed have styled herself as a “radical” (as the title of an early hidden-portrait in verse suggests), and was rapidly hailed as such by her peers, her revising practice opens up the spectrum of transformations to more ambiguous models. While her textual experiments betray a secret pull towards correction and propriety, her tinkering with words evokes the patient chiseling of the craftsman rather than the stroke of genius, or the fanciful errata of natural evolution over historical catastrophe. Wavering between abundant working notes and notoriously truncated publications, between exhaustiveness and silence, between endless starts and the ever-receding horizon of completion, Moore’s unstable corpus thus contributes to the redefinition of creative revolution.